Why Do Firms with Diversification Discounts Have Higher Expected Returns? - Mitton, Todd; Vorkink, Keith (Journal of Financial and Quantitative Analysis, 2010)
Abstract A diversified firm can trade at a discount to a matched portfolio of single-segment firms if the diversified firm has either lower expected cash flows or higher expected returns than the single-segment firms. We study whether firms with diversification discounts have higher expected returns in order to compensate investors for offering less upside potential (or skewness exposure) than focused firms. Our empirical tests support this hypothesis. First, we find that focused firms offer greater skewness exposure than diversified firms. Second, we find that diversified firms have significantly larger discounts when the diversified firm offers less skewness than matched single-segment firms. Finally, we find that up to 53% of the excess returns received on diversification-discount firms relative to diversification-premium firms can be explained by differences in exposure to skewness.